Improving Teacher's Job Satisfaction Through Principal Transformational Leadership and Organizational Justice - Hidayat, Rais; Patras, Yuyun Elizabeth; Marini, Arita; Sarifah, Iva; Nurjannah, Nurjannah (Graduate Program Magister Manajemen Pendidikan, 2023)
Teacher's job satisfaction is a crucial factor in maintaining the quality of education. The research aims to demonstrate the principal's transformational leadership role and organizational justice perceptions to improve teacher's job satisfaction. The quantitative design with survey methods used in this research. The research was conducted in Indonesia with a sample of 256 private high school teachers. Data analysis uses the analysis path on SMART PLS. Research findings: Teacher's job satisfaction can be improved by optimizing principal transformational leadership's role and enhancing the perception of organizational justice in schools. In this research, strengthening proposals based on transformational leadership indicators and organizational justice can prepare private school strategies and action plans to improve teacher's job satisfaction.